Pathway and mechanism of nitrogen transformation during composting: Functional enzymes and genes under different concentrations of PVP-AgNPs. (April 2018) - Zeng, Guangming; Zhang, Lihua; Dong, Haoran; Chen, Yaoning; Zhang, Jiachao; Zhu, Yuan; Yuan, Yujie; Xie, Yankai; Fang, Wei
Graphical abstract: Highlights: Functional enzymes activities and genes abundances were determined. Nitrogen was most conserved in the end with PVP-AgNPs at 10 mg/kg compost. The TN loss was most significantly correlated with bacterial amoA gene abundance. The dominant family of ammonia-oxidizing bacteria was Nitrosomonadaceae . Abstract: Polyvinylpyrrolidone coated silver nanoparticles (PVP-AgNPs) were applied at different concentrations to reduce total nitrogen (TN) losses and the mechanisms of nitrogen bio-transformation were investigated in terms of the nitrogen functional enzymes and genes. Results showed that mineral N in pile 3 which was treated with AgNPs at a concentration of 10 mg/kg compost was the highest (6.58 g/kg dry weight (DW) compost) and the TN loss (47.07%) was the lowest at the end of composting. Correlation analysis indicated that TN loss was significantly correlated with amoA abundance. High throughput sequencing showed that the dominant family of ammonia-oxidizing bacteria (AOB) was Nitrosomonadaceae, and the number of Operational Taxonomic Units (OTUs) reduced after the beginning of composting when compared with day 1. In summary, treatment with AgNPs at a concentration of 10 mg/kg compost was considerable to reduce TN losses and reserve more mineral N during composting.